Radiotherapy for Head and Neck Cancer: Evaluation of Triggered Adaptive Replanning in Routine Practice - Figen, Metin; Çolpan Öksüz, Didem; Duman, Evrim; Prestwich, Robin; Dyker, Karen; Cardale, Kate; Ramasamy, Satiavani; Murray, Patrick; Şen, Mehmet (Frontiers in Oncology, 2020)
Purpose and Objective: A proportion of patients receiving radiotherapy for head and neck squamous cell carcinoma (HNSCC) require ad hoc treatment replanning. The aim of this retrospective study is to analyse the patients who required ad hoc replanning and identify factors which may predict need for replanning. Materials and Methods: A single centre evaluation of all patients receiving radical or adjuvant (chemo)radiotherapy (CRT) for HNSCC between January-December 2016 was undertaken. Patients who underwent ad hoc replanning during the treatment were identified in electronic records. Reasons of re-planning were categorized as: weight loss, tumour shrinkage, changes in patient position and immobilization-related factors. Potential trigger factors for adaptive radiotherapy such as patient characteristics, primary tumour site, stage, concomitant chemotherapy, weight loss ratios, radical/adjuvant treatment, and nutritional interventions were investigated. Results: 31/290 (10.6%) HNSCC patients who underwent radical/adjuvant radiotherapy were required replanning. The adaptive radiotherapy (ART) was performed at a mean fraction of 15. The most common documented reasons for replanning were tumour shrinkage (35.5%) and weight loss (35.5%). Among the patient/tumour/treatment factors, nasopharyngeal primary site (p=0.013) and use of concurrent chemotherapy with radiotherapy (p=0.034) were found to be significantly correlated to the need for replanning. Conclusion: Effective on-treatment verification schedules and close followed up of patients especially with NPC primary and/or treated with concurrent chemoradiotherapy are crucial to identify patients requiring ART. We suggest an individualised triggered approach to ART rather than scheduled strategies since it is likely to be more feasible in terms of utilization of workload and economic resources.